Legado clássico no Renascimento e sua receção: contributos para a renovação do espaço cultural europeu - Cláudia Teixeira (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2017)
This volume brings together a set of articles that aim to show how the texts written by European authors, strongly influenced by classical tradition, contributed to the definition and treatment of values and perspectives within a polyhedric cultural space across several centuries.